Trajectory of socio-economic transformations in the contemporary concept of social changes - Герасимова E. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The proposed paper attempts to conceptualize the theory of social transformation in the context of contemporary changes in the social and economic sphere.